The Main Tools of Teaching a Foreign Language - Yusupovna, Qambarova Diloram (European Journal of Life Safety and Stability (2660-9630), 2023)
The implementation of the developed experiences of pedagogy and the achievements in education is one of the important conditions of today. This article provides information about the tools used in teaching a foreign language.